Correlation of β-adrenergic reactivity of erythrocyte membranes with clinical characteristics of patients with coronary artery disease and HF with preserved and reduced ejection fraction - E. F. Muslimova; V. A. Korepanov; T. Yu. Rebrova; S. L. Andreev; S. A. Afanasiev (Российский кардиологический журнал)
Aim. To evaluate β-adrenergic reactivity of erythrocyte membranes (β-ARM) depending on clinical parameters in patients with heart failure (HF) with preserved and reduced ejection fraction (EF), who had prior myocardial infarction.Material and methods. The sample included 89 patients with HF and past myocardial infarction. Preserved EF (HFpEF) group included 64 (71,9%) patients, while reduced ejection fraction (HFrEF) — 25 (28,1%) patients. All patients underwent β-ARM assessment using an inhibition of hemolysis in a hypoosmotic medium with β-blocker.Results. The groups with HFpEF and HFrEF were comparable in β-ARM values. There was no linear relationship between β-ARM and LVEF. In the HFpEF group, following differences in β-ARM were revealed depending on the HF functional class (p=0,049): 42,5 (24,1; 61,9) CU in class I, 25,9 (17,1; 36,9) CU in class II, 22,2 (14,9; 27,3) CU in class III. This was not observed in the HFrEF group (p=0,143). In HFpEF, patients with LV hypertrophy had (p=0,049) higher β-ARM values than patients without it (36,9 (24,2; 58,6) CU vs 23,3 (16,0; 29,8) CU). At the same time, in HFrEF, β-ARM was the same (p=0,364) in patients with and without LV hypertrophy. In the HFpEF group, patients taking angiotensin-converting enzyme inhibitors/angiotensin receptor blockers at admission had 2-fold lower β-ARM (p=0,035) than patients who did not take it.Conclusion. In the sample with past myocardial infarction, patients with HF with preserved and low EF had comparable β-ARM. At the same time, individuals with HFpEF and LV hypertrophy differed from patients without hypertrophy in increased β-ARM, i.e., higher sympathoadrenal system intensity and reduced adrenergic reactivity, which was not observed in the HFrEF group. In the HFrEF group, taking angiotensin-converting enzyme inhibitors/angiotensin receptor blockers was associated with more favorable indicators of adrenergic reactivity.